KARAKTERISASI ENZIM PEKTINASE YANG DIHASILKAN DARI ISOLAT KHAMIR INDIGENUS YANG DIISOLASI SELAMA FERMENTASI BIJI KOPI ROBUSTA - Fitri, Hasanul Fitri; Yanto, Subari; Praja Putra, Reski (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2025)
The following research aims to understand indigenous yeast isolates that are pectinolytic, the effect of incubation time on pectinase enzyme activity, and the pH and temperature properties of pectinase enzymes obtained from indigenous yeast resulting from spontaneous fermentation of robusta coffee beans. The following type of research is experimentation through RAL (Completely Randomized Design). This research first carried out selection of pectinolytic yeast, then determined the optimum incubation duration, pH and optimum temperature of the pectinase enzyme. The yeast isolate used was selected using media (1% pectin + 0.1% Congo red + 2% agar) to determine the highest pectinolytic ability. Selected pectinolytic yeast isolates will proceed to the stage of determining the optimum incubation time with periods of 24, 48, 72, 96, 120, and 144 hours, where every 24 hours enzyme extraction is carried out. Furthermore, the crude extract of the pectinase enzyme produced from selected pectinolytic yeast isolates was characterized at pH (3, 3.5, 4, 4.5, 5, 5.5, 6) and temperature (30oC, 40oC, 50oC, 60oC, 70oC) to determine the optimum pH and temperature. The research results showed that tests on seven indigenous yeast isolates were pectinolytic and the one with the highest pectinolytic ability was isolate K24I7 with a clear zone diameter of 3.13 mm. In determining the optimum incubation time, it was found that at an incubation time of 24 hours, isolate K24I7 was able to produce enzyme activity that was similar to other incubation times with a specific enzyme activity of 10.08 U/mg. The results of the characterization of the pectinase enzyme produced from isolate K24I7 were optimum at pH 5.5 with a specific enzyme activity value of 10.09 U/mg and an optimum temperature in the range of 40oC-60oC with an average specific enzyme activity of 10.08 U/mg. The pectinase enzyme produced from isolate K24I7 is thermophilic because it is still active at 70oC.